2013
DOI: 10.1016/j.virol.2013.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Treg depletion attenuates the severity of skin disease from ganglionic spread after HSV-2 flank infection

Abstract: Regulatory T cells (Tregs) attenuate lesion severity and disease after HSV ocular or genital infection, but their role in cutaneous infection remains unclear. Treg depletion (anti-CD25 mAb in C57BL/6 mice or diphtheria toxin (DT) in DEREG mice) prior to tk-deficient HSV-2 flank infection significantly decreased skin lesion severity, granulocyte receptor-1(Gr-1(+)) cell number, and chemokine (KC) expression in the secondary skin, but significantly increased immune effectors and chemokine expression (MCP-1, KC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Since adult DEREG mice do not develop autoimmunity after Treg depletion as it was observed in other mouse strains [28][30], this model is suitable to study the role of Tregs during infection without the side effects of autoimmune activation, as it was demonstrated in several models of chronic infection [6], [25], [31][33].…”
Section: Introductionmentioning
confidence: 84%
“…Since adult DEREG mice do not develop autoimmunity after Treg depletion as it was observed in other mouse strains [28][30], this model is suitable to study the role of Tregs during infection without the side effects of autoimmune activation, as it was demonstrated in several models of chronic infection [6], [25], [31][33].…”
Section: Introductionmentioning
confidence: 84%
“…During HSV-1 and HSV-2 infection of mice, cells phenotypically resembling MDSCs infiltrated the cornea (34) and skin (40,164). In one study, increased herpes simplex keratitis (HSK) and viral titers were observed in HSV-1-infected Kit W-sh mice (that lack CD31 + mast cells), compared to wildtype mice (130).…”
Section: Dna Virusesmentioning
confidence: 99%
“…Female adult C57BL/6 mice, 6 to 8 weeks of age, were purchased from the Animal Resource Centre (Perth, Australia) and acclimatized, and experiments were conducted with the approval of the Children's Medical Research Institute/Children's Hospital at Westmead animal ethics committee. To mimic the route of HSV infection in humans, we used an epicutaneous flank scarification skin infection model as previously described (34). Briefly, mice were anesthetized, the left flank was shaved and depilated (Nair), and then the mice were infected topically by applying 10 l of virus (1 ϫ 10 6 PFU) or PBS within a 2-mm 2 area on the flank skin, which was scarified 20 times using an 18-guage needle, and a dressing was applied after 1 h for 24 h to facilitate infection.…”
Section: Figmentioning
confidence: 99%